Adaptive image-based method for integrated multi-scale modeling of damage evolution in heterogeneous concrete. (May 2015) - Sun, Bin; Li, Zhaoxia
Highlights: An adaptive integrated multi-scale modeling approach is proposed. The approach can consider the real random heterogeneous meso-components. The approach can carry out automatically trans-scale failure analysis of concrete. The trans-scale process from meso-damage to structural failure can be simulated. Abstract: This paper presents a new adaptive image-based method for integrated multi-scale modeling and computational approach to simulate the trans-scale process of dynamic fracture in concrete structures from evolving meso-damage to structural failure. Two numerical examples are presented to demonstrate the accuracy and effectiveness of the approach. The results show that, the approach can be used to reveal the dynamic fracture mechanisms of concrete structures by considering the trans-scale coupling process from meso-damage to local failure in vulnerable area and eventually to structural failure; and it can obtain satisfactory results with sufficient precision and lower cost, especially for large scale computations.